2016
DOI: 10.1111/jcmm.12955
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 1 – an antioxidant enzyme in cancer

Abstract: Peroxiredoxins (PRDXs), a ubiquitous family of redox‐regulating proteins, are reported of potential to eliminate various reactive oxygen species (ROS). As a major member of the antioxidant enzymes, PRDX1 can become easily over‐oxidized on its catalytically active cysteine induced by a variety of stimuli in vitro and in vivo. In nucleus, oligomeric PRDX1 directly associates with p53 or transcription factors such as c‐Myc, NF‐κB and AR, and thus affects their bioactivities upon gene regulation, which in turn ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
142
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 124 publications
(172 reference statements)
3
142
0
1
Order By: Relevance
“…17,[32][33][34] Continuous inflammatory responses in intestinal tissues are considered as the prominent pathological features of IBS, especially IBS-D and PI-IBS. 16,33,[35][36][37] PRDX1 is associated with some tumors [21][22][23]38 and especially associated with colorectal cancer caused by chronic inflammation. 39,40 However, few studies have examined the relationship between PRDX1 and intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…17,[32][33][34] Continuous inflammatory responses in intestinal tissues are considered as the prominent pathological features of IBS, especially IBS-D and PI-IBS. 16,33,[35][36][37] PRDX1 is associated with some tumors [21][22][23]38 and especially associated with colorectal cancer caused by chronic inflammation. 39,40 However, few studies have examined the relationship between PRDX1 and intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In all IBS patients, the serum PRDX1 (r = .335, P < .001) and TNF-α 16,33,[35][36][37] PRDX1 is associated with some tumors [21][22][23]38 and especially associated with colorectal cancer caused by chronic inflammation. 39,40 However, few studies have examined the relationship between PRDX1 and intestinal inflammation.…”
Section: Correlation Of Ibs-sss With Prdx1 and Tnf-α In Patients Wimentioning
confidence: 99%
See 2 more Smart Citations
“…PRDX1 is an antioxidant enzyme, but its role in breast cancer is controversial. It is, however, clearly overexpressed in breast cancer tissue relative to normal tissue [70]. Recently, Bajor et al demonstrated that PRDX1 is involved in reducing exogenous oxidative stress and induces cell growth in breast cancer [71].…”
Section: Breast Cancermentioning
confidence: 99%